Electrotunable liquid sulfur microdroplets - Guangmin Zhou (Nature Portfolio, 2020)
Manipulating liquids with tunable shape and optical functionalities in real time remains a great challenge. Here, the authors demonstrate electrotunable liquid sulfur microdroplets in an electrochemical cell and tune its characteristics in a fast, repeatable, and controlled manner.